Pengaruh Kelaiklautan Kapal dan Sistem Kompensasi Terhadap Kepuasan Kerja Crew Kapal di PT. Salam Pasifik Indonesia Lines - Kuncowati; Mudiyanto (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2017)
This research was conducted at PT. Salam Pacific Indonesia Lines Surabaya (PT. SPIL), which is one of the national private shipping companies that play a role in the advancement of sea transportation in Indonesia. Crew ship is very important role in the progress of sea transport, especially the seafarers both inside and outside the country is necessary even to the lack of sailors, therefore the management of shipping companies should really pay attention to the welfare of the crew so the ship crew satisfied and comfortable working at PT. SPIL. This study aims to determine the influence seaworthiness and compensation system on job satisfaction crew on the ship owned by PT. Salam Pacific Indonesia Lines Surabaya. This research is quantitative. This research begins with sample determination then spread quisioner to 327 respondents in can statistic calculation with t test of variable of ship seaworthiness (X1), compensation system variable (X2) independently affect to (Y) job satisfaction. Variable X1 has significant effect, it is seen in the result of questionnaire about maritime shipiness need to be improved that is on the ship safety equipment of ship's crew. Safety tools must be in a ready-made state, which will be used at any time in case of emergency (fire on board, sinking ship, etc.). For variable X2 about the compensation system has an effect on the job satisfaction of the crew. With a decent wage and able to meet basic family needs it will be a major factor of job satisfaction. And based on the F test it is known that the velocity variable of the ship and the compensation system together affect the job satisfaction, F value counted 213,775 > F table 2,649. Based on the regression equation, it can be seen that the constant of 2,101 although without any change from X variable (ship capability and compensation system) will still increase by 2,101 but it is expected that ship velocity variable will be increased by 0,590 and compensation system is 0,274. PT. SPIL should maintain and even increase the velocity of the vessel and the compensation system for increased job satisfaction. Of the two variables, the variable that has the strongest influence on job satisfaction is the maritime boundary of the vessel, so it can be advisable to emphasize on the maritime boundary of the vessel. Capacity ship here in the sense of improving the safety system of the voyage. Due to the good sail safety system, the sailor's work satisfaction is increasing, guaranteed life safety on board during the voyage.